PENGARUH ETIKA UANG (MONEY ETHICS) TERHADAP KECURANGAN PAJAK (TAX EVASION) DENGAN RELIGIUSITAS, GENDER, DAN MATERIALISME SEBAGAI VARIABEL MODERASI (Studi pada WP OP yang Melakukan Kegiatan Usaha atau Pekerjaan Bebas di Pekanbaru) - Hafizhah, Ihsanul; Basri, Yessi Mutia; ', Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
The objective of the study therefore is to examine the relationship between money ethics and tax evasion as well as investigating the moderating effect of religiosity (intrinsic and extrinsic), gender, and materialism on the relationship . The population in this study is individual taxpayer that conducting business or employment free in Pekanbaru. Data this study uses primary data directly through a questionnaire. The data were analyzed to test the hypothesis using a simple linear regression analysis and Moderated Regression Analysis (MRA). Results from this study indicate that the first, the money ethics was related to tax evasion with t count 3,260,<t table 2,002 and significant 0,002>0,05. Second, intrinsic religiosity was moderate the relationship between money ethics and tax evasion with t count (-2,379),<t table (-2,003) and significant 0,021>0,05. Third, extrinsic religiosity was not moderate the relationship between money ethics and tax evasion. Fourth gender was moderate the relationship between money ethics and tax evasion with t count (-2,758),<t table (-2,003) and significant 0,008>0,05, the fifth materialism was moderate the relationship between money ethics and tax evasion with t count 8,010,<t table 2,003 and significant 0,000>0,05.Keywords: Tax Evasion, Money Ethics, Religiosity, Gender,and Materialism